Analisis Proses Komunikasi Organisasi dalam Penyusunan Standar Operasional Prosedur di Inspektorat Daerah Kota Serang - Rian Fikri Teguh Imanto; April Laksana; Putri Handayani; Achmad Nashrudin Priatna; Arfian Suryasuciramdhan (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
Standard Operating Procedures (SOPs) play a crucial role in creating consistency, efficiency, and accountability in governance. However, the process of developing SOPs within the bureaucracy often faces complex organizational communication challenges. This study aims to analyze the organizational communication process in developing SOPs at the Serang City Regional Inspectorate, focusing on the role of the Secretariat as the administrative coordination center. The method used was a qualitative case study approach, involving in-depth interviews with key informants, observation, and documentation analysis. The results indicate that organizational communication plays a crucial role in every stage of SOP development, from data collection and drafting, to cross-sector coordination, and document finalization. The Secretariat acts as a liaison between units, archives manager, and coordination meeting facilitator. However, obstacles identified include a top-down vertical communication pattern, differing perceptions between units, delays in information flow due to bureaucracy, and limited technology-based communication tools. Improvements were made through the establishment of cross-unit forums, communication training, and the use of online applications to strengthen two-way communication. The implications of this research indicate that increasing the effectiveness of organizational communication is a key factor in accelerating the process of preparing SOPs and supporting the creation of more responsive, efficient, and accountable governance.